Analog des Erdös-Wintnerschen Satzes für die Zahlenfolge der Werte von Polynome mit ganzzahligen Koeffizienten - Uždavinys, R. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Уждавинис. Аналог теоремы Эрдеша—Винтнера для последовательности значений целочисленного полинома R. Uždavinys. Erdešo—Vintnerio teoremos analogas polinomo su sveikais koeficientais reikšmių sekai